Fracture pain-Traveling unknown pathways - Alves,CJ (2016)
An increase of fracture incidence is expected for the next decades, mostly due to the undeniable increase of osteoporotic fractures, associated with the rapid population ageing. The rise in sports-related fractures affecting the young and active population also contributes to this increased fracture incidence, and further amplifies the economical burden of fractures. Fracture often results in severe pain, which is a primary symptom to be treated, not only to guarantee individual's wellbeing, but also because an efficient management of fracture pain is mandatory to ensure proper bone healing. Here, we review the available data on bone innervation and its response to fracture, and discuss putative mechanisms of fracture pain signaling. In addition, the common therapeutic approaches to treat fracture pain are discussed. Although there is still much to learn, research in fracture pain has allowed an initial insight into the mechanisms involved. During the inflammatory response to fracture, several mediators are released and will putatively activate and sensitize primary sensory neurons, in parallel, intense nerve sprouting that occurs in the fracture callus area is also suggested to be involved in pain signaling. The establishment of hyperalgesia and allodynia after fracture indicates the development of peripheral and central sensitization, still, the underlying mechanisms are largely unknown. A major concern during the treatment of fracture pain needs to be the preservation of proper bone healing. However, the most common therapeutic agents, NSAIDS and opiates, can cause significant side effects that include fracture repair impairment. The understanding of the mechanisms of fracture pain signaling will allow the development of mechanisms-based therapies to effectively and safely manage fracture pain.